Prevalence of Methicillin-Resistant Staphylococcus sp. (MRS) in Different Companion Animals and Determination of Risk Factors for Colonization with MRS - Igor Loncaric; Alexander Tichy; Silvia Handler; Michael P. Szostak; Mareike Tickert; Magda Diab-Elschahawi; Joachim Spergser; Frank Künzel (MDPI AG, 2019)
The aim of this study was to detect the prevalence of methicillin-resistant Staphylococcus sp. (MRS) in populations of companion animals that either have previously been exposed or have not been exposed to antibiotic therapy or veterinary facilities, and if owners’ healthcare profession had an influence on colonization with MRS. In addition, the antimicrobial resistance pheno- and genotype were investigated and risks for colonization with MRS were assessed. During this study, 347 nasal swabs (dogs n = 152; cats n = 107; rabbits n = 88) were investigated for the presence of methicillin-resistant Staphylococcus aureus (MRSA). In addition, 131 nasal swabs (dogs n = 79; cats n = 47; rabbits = 3; guinea pigs = 2) were examined for the presence of MRSA but also other MRS. In total, 23 MRS isolates belonged to nine staphylococcal species: Staphylococcus epidermidis (n = 11), Staphylococcus warneri (n = 3), Staphylococcus hominis (n = 2), Staphylococcus pseudintermedius (n = 2), and singletons Staphylococcus cohnii, Staphylococcus sciuri, Staphylococcus fleurettii, Staphylococcus lentus, and Staphylococcus haemolyticus. Twenty isolates displayed a multidrug-resistant phenotype. Various resistance and biocide resistance genes were detected among the examined staphylococci. Risk assessment for MRS colonization was conducted using a number of factors, including animal species, breed, age, gender, recent veterinary health care hospitalization, and antibiotic prescription, resulting in recent veterinary health care hospitalization being a significant risk factor. The detection of multidrug-resistant MRS in healthy animals is of importance due to their zoonotic potential.